2023
DOI: 10.3390/plants12071421
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Activity of Canadian Goldenrod (Solidago canadensis L.) Extracts on Seed Germination and Growth of Lettuce (Lactuca sativa L.) and Garden Pepper Cress (Lepidium sativum L.)

Abstract: Native to N. America, Canadian goldenrod (Solidago canadensis L.) was introduced to Europe as an ornamental plant and quickly spread here and in other parts of the world. The rapid spread of the plant is due to several reasons: phenotypic plasticity, broad climatic tolerance, propagation via underground rhizomes and seeds that mature in large numbers, etc. Additionally, the success of Canadian goldenrod’s invasion is determined by its allelochemicals that affect seed germination, root formation and whole growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…On the other hand, S. virgaurea was considered to be a taxon with low competitive ability that is commonly displaced from its habitat by invasive goldenrods [ 54 ]. In addition, it was found that the allelopathic activity of S. virgaurea root and inflorescence extracts was higher than those of S. canadensis and S. ×niederederi [ 55 ]. This activity likely improves its survival in mixed-species stands as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, S. virgaurea was considered to be a taxon with low competitive ability that is commonly displaced from its habitat by invasive goldenrods [ 54 ]. In addition, it was found that the allelopathic activity of S. virgaurea root and inflorescence extracts was higher than those of S. canadensis and S. ×niederederi [ 55 ]. This activity likely improves its survival in mixed-species stands as well.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous ethanolic extracts of the roots and rhizomes of S. canadensis inhibited the germination and growth of different plant species and the mycorrhizal fungal population in its rhizosphere soil [ 60 ]. Meanwhile, the root essential oil, which was dominated by limonene and β -pinene, suppressed the germination of lettuce seeds and showed significant inhibitory effects on the growth of lettuce and garden pepper cress [ 55 ]. In this way, the effects of the extracts on other species make them potentially useful as bioherbicides that can be used to help manage a range of pest and disease problems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent S. canadensis metabolic analysis has revealed the existence of 122 metabolites, including flavonoids, phenylpropanoids, and terpenoids [70], which provide the plant allelopathic potential. Others found that S. canadensis affects the growth and seed germination of tested plants (Lactuca sativa, Morus alba, Pharbitis nil, Brassica campestris, Lepidium sativum, and others) [71][72][73]. The allelopathic effect was also observed in the research by Perera et al [74] where S. canadensis leaf and flower extracts caused lower germination and seedling growth of different grassland plant species such as Festuca rubra L., Phleum pratense L., Poa pratensis L., Lotus corniculatus L., Trifolium repens L., and Silene flos-cuculi (L.) Greuter & Burdet.…”
Section: Behind the Invasiveness Of S Canadensismentioning
confidence: 99%